Applying Graph Databases and Human Mobility Data to Track Infectious Disease Spread in Brazil - Mariama C. S. de Oliveira; Lucas Henrique G. de Sales; Andrêza Leite de Alencar; Natalia T. S. de Oliveira; Antônio Ricardo K. Cunha; Pablo Ivan P. Ramos (Journal of Information and Data Management, 2025)
This work has been enriched by the invaluable contributions of the following institutions: The ÆSOP (Alert-Early System of Outbreaks with Pandemic Potential) project provided us with the primary idea and guidance for this research, laying the foundation for our study. CIn-UFPE, SiDi, and Samsung Brazil, who supported the ``Data Engineering and Data Science’’ Residency program, where this study was successfully applied as part of our coursework, culminating in its completion. The UFRPE collaborative efforts and orientation support played a pivotal role in the successful execution and completion of this research project.